Penerapan Model UTAUT Untuk Mengevaluasi Penerimaan dan Penggunaan E-learning Smartschool (Studi Kasus : SMA Negeri 96 Jakarta) - Siti Khofifah Munjiyanti; Kraugusteeliana Kraugusteeliana; Anita Muliawati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
E-learning Smartschool is one of the Smarteschool services used at SMAN 96 Jakarta since the Covid-19 pandemic in 2020. E-learning Smartschool is used as a media for distance learning at SMAN 96 Jakarta with the hope that teaching and learning activities during the pandemic can continue. So the UTAUT model is proposed to measure student acceptance of SMAN 96 Jakarta on the use of e-learning Smartschool. Unified Theory of Acceptance and Use of Technology is a theoretical framework consisting of four independent variables, two dependent variables and four moderating variables that function to measure the acceptance and use of information systems. This study uses the PLS-SEM data analysis method with data from questionnaires distributed to 271 students of SMAN 96 Jakarta. This study found that behavioral intention (BI) was significantly influenced by performance expectations (PE), business expectations (EE) and social influence (SI) which was 57.8% while use behavior (UB) was significantly influenced by facilitating conditions (FC) and behavioral intention (BI) which is 52.1%. It can be concluded that Smartschool E-learning can be accepted and used by students of SMAN 96 Jakarta as a supporting medium for distance learning during the Covid-19 pandemic.